The effect of sales, cash turnover and receivables turnover in increasing net profit in Consumer Goods Industry sector companies - Radiyah Julizar; Fery Citra Febriyanto (Privietlab, 2021)
This study aims to determine the effect of sales, cash turnover, and accounts receivable turnover on net income in consumer goods industrial sector companies listed on the Indonesia Stock Exchange. The research period used is 2016-2020. The population in this study are all companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period as many as 53 issuers. The method used in this research is a quantitative research method. The sampling technique used purposive sampling so that 23 issuers were produced as research samples. This study uses descriptive data analysis techniques and panel data regression analysis with e-views 12 software tools. The results show that simultaneously sales, cash turnover and accounts receivable turnover have a significant effect on net income. Partially, sales have a significant effect on net income, cash turnover has no significant effect on net income, accounts receivable turnover has no significant effect on net income